Enhancement of Operating Voltage and Temperature Range by Adding Lithium bis(fluorosulfonyl)imide as Electrolyte Additive. Issue 44 (27th November 2020) - Han, Songyi; Liu, Shuling; Gao, Jingxiong; Wu, Jie; Yang, Yang; Yan, Tingfang; Sun, Yuanyu; Bao, Luri; Tang, Weiping
Abstract: Electrolytes consisting of carbonate solvents and LiPF6 readily decompose at high operating voltages, causing poor battery performances. In order to meet the needs of high voltage and high specific energy cells, electrolytes with improved electrochemical stabilities are urgently required. Here, we have introduced the lithium bis(fluorosulfonyl)imide (LiFSI) as an electrolyte additive to accomplish this goal. Through the research in this paper, it is found that the electrolyte system with LiFSI can form more stable and uniform solid electrolyte interphase (SEI) film during the cycle, which can be used to suppress the decomposition of carbonate‐based electrolytes. Subsequently, this finding is supported by the density functional calculations and the structural analysis. LiNi0.5 Co0.2 Mn0.3 O2 /graphite full cells with different amounts of LiFSI additive are fabricated to demonstrate the improvement of electrochemical performance. Working at 4.4 V and 1 C, the capacity retention rate of cells with 5 wt.% LiFSI is significantly enhanced compared with non‐LiFSI (52.4 % for none and 85.0 % for 5 wt. % loading at room temperature after 120 cycles; 47.5 % for none and 80.0 % for 5 wt. % loading at 45 °C after 100 cycles). Abstract : Electrolytes consisting of carbonate solvent and LiPF6 are readily to decompose at highly operated voltage. Here, we introduce the electrolyte additive of lithium bis(fluorosulfonyl)imide (LiFSI) to address this issue. By adding LiFSI, a stable and uniform solid electrolyte interphase (SEI) film can be formed to suppress the decomposition of carbonate solvent and LiPF6, subsequently corroborated by density functional calculations. LiNi0.5 Co0.2 Mn0.3 O2 /graphite full cells based on different amounts of LiFSI additive are fabricated to demonstrate the electrochemical improvement.